A Study of the Alignment of SDSS DR16 galaxies at REDSHIFT 0.24 to 0.27 - Malla, Janak Ratna; Saurer, Walter; Aryal, Binil (Academia Research Journal, 2026)
We studied the spatial orientation of spin vectors of 1715 SDSS DR16 galaxies within the redshift range of 0.24 to 0.27 using the u-band imaging (λeff ≈ 355 nm). This study analyzed a total of 1715 galaxy samples to provide new insights into the formation and evolution of galaxies and help interpret observational data. Adopting Flin& Godlowski method, we transformed the two-dimensional projected images into three-dimensional spin vector components: specifically, polar (θ) and azimuthal (ϕ) angles and studied the angular momentum alignment. Through the four simultaneous tests chi-square, auto-correlation, and Fourier analysis statistical tests, we concluded that the SDSSDR16 data of 1715galaxies support strong anisotropy in the polar angle distribution and point toward isotropy in the azimuthal angle distribution. These finding supports the Hierarchical model of the galaxy evolution theory.